A study on the use and effect of design on child's bedroom - Agleron, Margaret Patricia S. (1995.)
Children's rooms are often designed in such a manner that the sole priority is of how nice the room attain the real cause of designing a child's bedroom. First, what needs to be understood is that learning does not only take place in school. Actually, education begins at home. Then enrichment and schooling should be coordinated so that there is a fast and synchronized program for absorbing knowledge. Design of the room serves as a medium to attain this purpose. Aside from applying the standard principles and elements of design careful planning should be taken into consideration to fully utilize the environment and to encourage the child to balance his development and growth. Certain features of a design provides a decorative, safe, practical and educational setting. Hence, applying these features could accomplish the absolute motive.
Term Paper (BID)--University of the Philippines Diliman
Keywords: Children's rooms -- Philippines